Ouverture de ‘Market-Space Management’ - Silvio M. Brondoni (Symphonya, 2002)
In global markets, corporations compete according to the new rules of market-space competition, that is within competition boundaries in which space is not a known, stable element in the decision-making process. It is, instead, a competitive factor, shaped and modified by the actions and the reactions of corporations and governments. Global networks operating in enlarged competition spaces (thus exploiting the value of intangible assets such as brand equity, information systems and corporate culture) have market information at their disposal which is often sufficiently extensive and sophisticated to put them in a position to compete with governments in establishing the guidelines for local development. The over-supply condition that characterizes the richest markets today pushes companies into a neo-liberalism spiral. Over-supply conditions, moreover, often induce short-term results to be given too much importance, with a focus on the resources invested and the elimination of costs related to local social development.